The Effects of Remuneration and Employee Engagement towards Employees’ Performance: A Study on PT INTI (Pasero) Bandung, Indonesia - Tarmidi, Didi; Rahmayati Putri, Rizka; Gusni,; Agustriana, Darwis (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the remuneration, employee engagement, and employee performance at PT. INTI (Persero) Bandung and to find out how much the influence of the remuneration and employee engagement have on employee performance at PT. INTI (Persero) Bandung. Regarding the remuneration provided by the company, it is considered that it is in accordance with the agreement and the applicable provisions in the company so that the employee does not experience shortages in terms of the remuneration earned. And the company treats the employees well so that a positive and close family relationship between the company and employees is formed. But the performance that employees provide is still considered to be not maximal by the company, even though the remuneration provided is appropriate and there is a positive relationship between the company and employees. The research used a descriptive-verification method. The sample used in this study is the employees who work at PT. INTI (Persero) Bandung. The data processing is done by using multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. Based on the results of the study, it can be concluded that there is an influence between the remuneration and the performance of employees of PT. INTI (Persero) Bandung. And there is an influence between employee engagement and the performance of employees of PT. INTI (Persero) Bandung. The remuneration and employee engagement simultaneously affect the performance of employees of PT. INTI (Persero) Bandung.